Developing a green accountability success index for zakat management organizations - Azwar, Azwar; Andi Wawan Mulyawan (Center for Islamic Economics and Development Studies [P3EI], 2026)
Purpose – This study aims to develop the Green Accountability Success Index (GASI) as a standardized measurement instrument to assess the implementation of green accountability in Zakat Management Organizations (ZMOs). The index integrates Sharia principles with global sustainability and accountability frameworks in response to increasing demands for environmentally responsible Islamic social finance governance.Methodology – A mixed-methods approach was employed, combining qualitative and quantitative techniques. Variables and indicators were developed through a literature review and expert validation, while index weighting and computation used the multi-stage weighted index method to ensure systematic and proportional measurement.Findings – This study establishes a GASI framework consisting of six core variables: environmentally oriented financial accountability, sustainable governance, environmental awareness and action, mustahiq socio-economic sustainability, Sharia compliance and maqasid al Sharia, and technological innovation for green accountability. The index operates on a 0–1 scale and classifies performance into five levels, grouped into three implementation stages— traditional, developing, and advanced. This framework enables a comprehensive assessment of ZMO performance across zakat collection, distribution–utilization, and reporting activities.Implications – GASI serves as a practical evaluative tool for practitioners and regulators to design, monitor, and improve sustainable zakat governance, while supporting evidence-based policies that enhance transparency, environmental responsibility, and long-term socio-ecological impact. Academically, it provides a reference framework for future research on sustainability-oriented Islamic accountability.Originality – This study is among the first to operationalize green accountability in Islamic social finance through an integrated index-based framework, advancing both theory and practice.